Pertanggungjawaban Pidana terhadap Tindakan Pembajakan Film di Aplikasi Tiktok - Emiliana Febriyanti Alda Jalut; Orpa Ganefo Manuain; Adrianus Djara Dima (International Forum of Researchers and Lecturers, 2024)
This research is conducted with the aim of discussing and analyzing answers to problems such as the forms of actions that can be categorized as criminal acts of film piracy and the qualifications of criminal acts of film piracy on TikTok social media and how criminal liability for acts of film piracy in the TikTok application with regard to positive law in Indonesia. This research method is normative juridical method. Normative juridical method is a legal research method that focuses on library materials or secondary materials. With the approach used by researchers is a statutory approach and a conceptual approach. Based on the results of the research, benefits were obtained. The benefits obtained can be seen from the increase in likes and followers. Then the researcher also concluded that the act of piracy is categorized as a qualified offense with criminal aggravation which is included in the category of voorgezete handelings. In overcoming the existing problems, researchers argue that Tiktok also needs to be held accountable considering the losses caused are not small. However, researchers found that the legislation, especially Law Number 28 of 2014 concerning Copyright, does not separate sanctions for individuals and corporations. According to the author, there needs to be a separation of sanctions because the comparison of losses caused by actions taken by individuals and those taken by corporations is different.